2021
DOI: 10.2478/fman-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Leadership: A Study of Organizations Based in the United Arab Emirates

Abstract: The successful practice of innovation in any organization demands the integration and interaction of individual, collective, and organizational climate levels of management. Leadership styles have an impact on all these three levels of management. However, little work has been done to assess this impact, especially in the context of United Arab Emirates (UAE)-based organizations. This study was conducted with the purpose of assessing whether leadership processes, tools, and techniques differ in innovative orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
10
0
2
Order By: Relevance
“…This is considered the main motivation for leaders to create employee engagement with the organization. Transformational leaders are attractive because they always believe in employees, are change agents and always pay attention to improving the working capacity of employees in the organization, and organize the learning process so that the organization can cope with complexity as well as being very proactive in building an atmosphere of job satisfaction and engagement to leadership performance (Agarwal & Gupta, 2021). According to Burns (1978) transformational leadership has some values such as justice, fairness, honesty, and honor, which are the ultimate values that cannot be bargained or exchanged so that they can unleash their creativity, so leaders get great power through the mobilization of collective intelligence, new ideas and are an important condition for building learning organizations practice that not all leadership styles create these values (Moradi Korejan & Shahbazi, 2016).…”
Section: Transformational Leadership Stylementioning
confidence: 99%
“…This is considered the main motivation for leaders to create employee engagement with the organization. Transformational leaders are attractive because they always believe in employees, are change agents and always pay attention to improving the working capacity of employees in the organization, and organize the learning process so that the organization can cope with complexity as well as being very proactive in building an atmosphere of job satisfaction and engagement to leadership performance (Agarwal & Gupta, 2021). According to Burns (1978) transformational leadership has some values such as justice, fairness, honesty, and honor, which are the ultimate values that cannot be bargained or exchanged so that they can unleash their creativity, so leaders get great power through the mobilization of collective intelligence, new ideas and are an important condition for building learning organizations practice that not all leadership styles create these values (Moradi Korejan & Shahbazi, 2016).…”
Section: Transformational Leadership Stylementioning
confidence: 99%
“…Based on table 7, the results of interviews with respondents related to indicators, it is found that the trust from superiors to subordinates is following expectations but still following authority so that attendants are freer to carry out their duties. The confidence from managers to associates follows one of the characteristics of transformational leadership: leaders must be visionary and believe in assistants (Agarwal & Gupta, 2021), giving this indicator a Moderately Satisfied rating. has become a role model for me because my VP is extensive, and there are several things that he understands and teaches me.…”
Section: Senior Manager Of Budgetingmentioning
confidence: 99%
“…Still, not all employees are excited only by motivation and because sufficient operations are often given very briefly. Leaders motivate subordinates to improve performance (Agarwal & Gupta, 2021) and provide expectations to members about achievable goals (Bass & Riggio, 2006), so the assessment given with some notes is Moderately Satisfied. Based on table 11, the results of interviews with respondents related to indicators of innovation from leaders have not been felt by respondents because they tend to get stuck with existing work and take up time so that opportunities for brainstorming with leaders do not exist, this is not in line with the characteristics of transformational leadership, namely looking for problem-solving from different perspectives and suggesting new ways of doing things (Bass & Riggio, 2006), For this reason, a value of Not satisfied on the Innovation indicator is given.…”
Section: Senior Manager Of Budgetingmentioning
confidence: 99%
“…Os liderados são agentes de mudança e sempre estão atentos à melhoria da capacidade de trabalho dos funcionários na organização, além de serem muito proativos na construção de uma atmosfera de satisfação no trabalho e engajamento no desempenho da liderança (Downton, 1973;Burns, 1978;Bass, 1985;Avolio et al, 1988;Bass & Avolio, 1990;Judge & Piccolo, 2004;Agarwal & Gupta, 2021) explicam que a liderança transformacional tem alguns valores como justiça, equidade, honestidade e honra, que não podem ser trocados para que os liderados possam liberar sua criatividade.…”
Section: Estilo De Liderançaunclassified